Społeczna ocena transformacji systemowej w kontekście nierówności społecznych - Leśniak-Moczuk, Krystyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2007)
Celem artykułu jest zaprezentowanie poglądów polskich ekonomistów na społeczny kontekst transformacji ustrojowej. Zwrócono uwagę na społeczny odbiór nierówności społecznych, etyczne podstawy zachowań społecznych, wpływ zasad ustrojowych na kształtowanie się postaw jednostek funkcjonujących w systemach społeczno-ekonomicznych oraz na społeczne skutki transformacji systemowej.

The aim of the article is to present the Polish economists’ views on the social context of the political system transformation. What was highlighted was the social perception of social inequities, ethic basis of social behaviours, influence of political system principles on shaping attitudes of the individuals functioning in social and economic systems, as well as the social effects of the transformation.
Social Assessment of the System Transformation in the Context of Social Inequality